Acute Complication After Heat Stroke in a Half Marathon Healthy Participant: Literature Review - Babulovska, Aleksandra; Simonovska, Natasha; Pereska, Zanina; Kostadinoski, Kristin; Naumoski, Kiril (Turkiye Klinikleri, 2022)
Heat stroke is a set of symptoms that include a severe rise of body temperature that is usually but not always higher than 40ºC. Clin- ically, it is characterized by central nervous system dysfunction such as ataxia, delirium or cramps, in conditions of exposure to hot weather or strenuous physical exertion. We presented a 46-year-old male athlete who collapsed during a half marathon after running 20 km and 640 m in 2 hours and 2 minutes. He was brought to the clinic in an unconscious state febrile 38.6ºC with fasciculations, convulsions, hypotensive, tachycardic. During hospitalization with rhabdomyolysis and hypoxic hepatitis. It is crucial to recognize the clinical symptoms and signs in the acute phase of heat stroke and in areas with temperate continental climate, to begin timely treatment, to reduce mortality. Complications of heat stroke need to be diagnosed, appropriate treatment provided, to improve the prognosis of these conditions.
Keywords: Heat stroke; half marathon; rhabdomyolysis; hypoxic hepatitis